Evaluation of the triangle-relationship of industrial pollution, foreign direct investment, and economic growth in China’s transformation - Zhang, Juanfeng; Han, Rui; Song, Zongjun; Zhang, Lihua (Frontiers in Environmental Science, 2023)
Unlike previous research on foreign direct investment (FDI), economic growth, and pollution, this study focuses on investigating complex interactions specifically. A dynamic simultaneous equation model is adopted, together with the one-step systematic GMM, drawn upon to empirically analyze 30 Chinese provinces between 2006 and 2017. The results show that FDI does promote economic growth in China which, in turn, positively affects FDI. However, FDI inflow and economic growth both have negative environmental effects. A higher level of environmental pollution corresponds with FDI becoming more attractive. In the case of China, therefore, the pollution-haven hypothesis holds weight. Specifically, industrial environmental pollution is found to positively affect economic growth, indicating this growth to fall on the left side of the environmental Kuznets Curve. Accordingly, therefore, policymakers should look to optimize China’s industrial structure, guide the inflow of high-quality FDI, and promote healthy and sustainable development under the country’s new development philosophy.